ANALISIS KESESUAIAN KAWASAN KONSERVASI MANGROVE DI MUARA GEMBONG, KABUPATEN BEKASI PROVINSI JAWA BARAT - Tasim Suryadi; Fredinan Yulianda; Handoko Adi Susanto (EnviroScienteae, 2021)
The mangrove ecosystem in Muara Gembong, Bekasi Regency, has experienced degradation due to land use changes that have triggered abrasion, tidal flooding, intrusion and inundation. The mangrove ecosystem has a role and function in maintaining the balance of coastal areas. This study aims to analyze the suitability of mangrove conservation land based on land suitability parameters and biophysical conditions. The determination of conservation land was carried out by purposive sampling based on satellite images which were processed using the geographic information system (GIS) application with the overlapping method. The results showed that the location of Muara Bendera, Muara Pecah, Muara Kuntul and Muara Jaya Very Suitable (S1) was proposed as a mangrove conservation area. The locations of Muara Bungin and Muara Blacan are included in the appropriate category (S2) for conservation land. Determining the suitability of mangrove conservation areas can be important information for policy makers in realizing the sustainability of the mangrove ecosystem in Muara Gembong.